Association between cholesterol crystals and culprit lesion vulnerability in patients with acute coronary syndrome: An optical coherence tomography study. (April 2016) - Dai, Jiannan; Tian, Jinwei; Hou, Jingbo; Xing, Lei; Liu, Shengliang; Ma, Lijia; Yu, Huai; Ren, Xuefeng; Dong, Nana; Yu, Bo
Abstract: Background: Cholesterol Crystals (ChCs) are recognized as a hallmark of advanced atherosclerotic lesions. Previous animal and histopathology studies have revealed that Cholesterol crystallization trigger a local inflammatory response and plaque rupture. We sought to investigate the in vivo relationship between ChCs and culprit lesion vulnerability in patients with acute coronary syndrome (ACS). Methods: 206 culprit lesions from 206 patients with ACS who underwent optical coherence tomography (OCT) imaging were divided into 2 groups based on the presence or absence of ChCs. Culprit lesions characteristics were compared between ChCs and Non-ChCs groups. Results: For overall ACS patients, culprit lesions with ChCs had higher incidence of macrophages accumulation (77.8% vs. 40.0%, p < 0.001), microchannel (67.9% vs. 24.8%, p < 0.001), plaque rupture (58.0% vs. 36.0%, p = 0.001), thrombosis (66.7% vs. 49.6%, p = 0.016) and spotty calcification (35.8% vs. 10.4%, p < 0.001). In addition, the mean lipid arc (274.2 ± 57.6° vs. 228.1 ± 66.3°, p < 0.001) was larger and the lipid index (3826.1 ± 2111.4 vs. 2855.0 ± 1753.0, p = 0.001) was greater. The frequency of ChCs was significantly higher in patients with STEMI, as compared with NSTEACS (50.8% vs. 34.7%, p = 0.032). Larger lipid arc, higher incidence of macrophages accumulation and that of microchannel were observed in culprit lesions with ChCs in both STEMI (p = 0.028, p < 0.001, and p = 0.002 respectively) and NSTEACS (p < 0.001, p < 0.001, and p < 0.001 respectively) subgroups. Conclusion: ChCs were frequently associated with characteristics of vulnerable plaques in ACS culprit lesions as well as in STEMI and NSTEACS subgroups. ChCs and vulnerable plaque features were more often observed in culprit lesions of STEMI patients compared to NSTEACS patients. Highlights: OCT-Cholesterol crystals (ChCs) was associated with culprit lesion vulnerability in patients with acute coronary syndrome (ACS). ChC plays a critical role in lipid necrotic core formation, local inflammation, and plaque rupture. ChCs is associated with patients clinical manifestation (STEMI or NSTEACS).